2021
DOI: 10.1101/2021.10.07.21264568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using brain cell-type-specific protein interactomes to interpret genetic data in schizophrenia

Abstract: Genetics have nominated many schizophrenia risk genes that lack functional interpretation. To empower such interpretation, we executed interaction proteomics for six risk genes in human induced neurons and found the resulting protein network to be enriched for common variant risk of schizophrenia in Europeans and East Asians. The network is down-regulated in layer 5/6 cortical neurons of patients and can complement fine-mapping and eQTL data to prioritize additional genes in GWAS loci. A sub-network centered o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Although we did not observe an analogous enrichment for common variants of ASDs in the network, this could be due to power limitations of the ASD GWAS. In a parallel study, 71 we generated an iN-derived PPI network for SCZ-associated genes prioritized from well-powered GWAS data, showed that the network is enriched for common variant risk of SCZ, and used it to complement fine-mapping and expression quantitative trait loci (eQTL) co-localization approaches to prioritize additional genes from GWAS loci. Performing similar analyses on the ASD PPI network when larger ASD GWAS become available may reveal whether rare and common variants of ASDs converge onto shared pathways represented in the network, as we have already observed for the transcriptional circuit regulated by IGF2BP1-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not observe an analogous enrichment for common variants of ASDs in the network, this could be due to power limitations of the ASD GWAS. In a parallel study, 71 we generated an iN-derived PPI network for SCZ-associated genes prioritized from well-powered GWAS data, showed that the network is enriched for common variant risk of SCZ, and used it to complement fine-mapping and expression quantitative trait loci (eQTL) co-localization approaches to prioritize additional genes from GWAS loci. Performing similar analyses on the ASD PPI network when larger ASD GWAS become available may reveal whether rare and common variants of ASDs converge onto shared pathways represented in the network, as we have already observed for the transcriptional circuit regulated by IGF2BP1-3.…”
Section: Discussionmentioning
confidence: 99%
“…Our data not only empower hypothesis generation to study the mechanisms of individual ASD-associated genes but also suggest convergent pathways that may inform therapeutic intervention or clinical stratification strategies. More generally, the approach described in this study and the parallel SCZ study 71 can be expanded to generate larger PPI networks across brain cell types and neurodevelopmental stages to uncover novel pathways underlying psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pintacuda et al(51) and Hsu et al(52) demonstrated that mapping experimental, cell type-specific protein-protein interaction networks for GWAS gene products has great potential for understanding complex disease pathobiology. Their experiments were conducted in brain cells, mapping connections between (among others) GWAS genes associated with neurological disorders and found that the interactomes were enriched for genes related to the pathogenesis of the respective diseases.…”
Section: Discussionmentioning
confidence: 99%
“…pioneer/settler models show TFBSs are often >50 bp apart in REs) PPIs (Martin et al 2023). By weighing known direct/indirect PPIs in the context of TG regulation, NetREm helps characterize existing PPINs at a cell-type level (Johnson et al 2021;Murtaza et al 2022;Hsu et al 2022). It also helps address the link prediction problem, flagging undiscovered PPIs for follow-ups (Singh and Vig 2017).…”
Section: Discussionmentioning
confidence: 99%